Analysis of English Word Dominance in Júnior High School Textbooks and Implementation and Impact on Global Society - Komari, Komari; Lilik Yulianingsih; Purwo Haryono; Isry Laila Syathroh; Henny Sanulita (Mimbar Ilmu, 2025)
Low student interest in reading English textbooks and limited access to quality reading materials hinder vocabulary acquisition and students' adaptability in global contexts. This study aims to analyze the influence of English textbooks on students' reading interest, vocabulary mastery, and critical thinking skills. A quantitative approach was employed using a survey method. The sample consisted of 769 junior high school students selected randomly. The data were collected through a validated Likert-scale questionnaire (1–5) designed to measure students’ reading interest and vocabulary comprehension. Data analysis was conducted using descriptive statistics with SPSS version 29.0 to identify patterns and trends. The results reveal that access to English books, both at home and at school, significantly contributes to increased reading interest and vocabulary understanding among students. The study concludes that the availability of engaging and level-appropriate English reading materials plays a critical role in supporting students’ global literacy. The implication is that improving the quality and accessibility of English books can enhance students’ academic and social development in response to the demands of the 21st century.